2011
DOI: 10.1016/j.resuscitation.2010.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Variation in out-of-hospital cardiac arrest resuscitation and transport practices in the Resuscitation Outcomes Consortium: ROC Epistry–Cardiac Arrest

Abstract: Objectives-To identify variation in patient, event, and scene characteristics of out-of-hospital cardiac arrest (OOHCA) patients assessed by emergency medical services (EMS), and to investigate variation in transport practices in relation to documented prehospital return of spontaneous circulation (ROSC) within eight regional clinical centers participating in the Resuscitation Outcomes Consortium (ROC) Epistry-Cardiac Arrest.Methods-OOHCA patient, event, and scene characteristics were compared to identify vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 42 publications
4
66
0
1
Order By: Relevance
“…Therefore, it is important that all studies examining the effect of practitioner factors in OHCA consider the influence these factors will also have on the decision to attempt resuscitation to prevent misinterpretation of results. 28 We found that patient survival decreased when paramedics had not treated an OHCA for >6 months. This period of time is similar to the time in which ALS skills deteriorate (6-12 months) after training.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, it is important that all studies examining the effect of practitioner factors in OHCA consider the influence these factors will also have on the decision to attempt resuscitation to prevent misinterpretation of results. 28 We found that patient survival decreased when paramedics had not treated an OHCA for >6 months. This period of time is similar to the time in which ALS skills deteriorate (6-12 months) after training.…”
Section: Discussionmentioning
confidence: 72%
“…1 Despite efforts to improve all aspects of the chain of survival, there is significant and important variation in the process and outcome of care among those treated for OHCA by emergency medical services (EMS) providers or admitted to hospital after successful resuscitation efforts. [2][3][4][5] This variation is incompletely explained by http://dx.doi.org/10.1016/j.resuscitation.2015.04.015 0300-9572/© 2015 Elsevier Ireland Ltd. All rights reserved. patient and EMS factors typically measured to standardize reporting of the process and outcomes of care for OHCA in an attempt to facilitate comparisons between communities.…”
Section: Introductionmentioning
confidence: 99%
“…3 Despite robust systems of care for patients with trauma and rapidly evolving systems of care for patients with ST-segment-elevation myocardial infarction (STEMI) and stroke, the majority of communities do not achieve optimal survival after OHCA because of large discrepancies in resuscitation-related processes of care. [4][5][6] As a result, survival to hospital discharge varies significantly both across different regions and by presenting rhythm. 7,8 Survival increases significantly if the OHCA is quickly recognized and responded to with prompt activation of 9-1-1, bystander-initiated cardiopulmonary resuscitation (CPR), bystander and/or basic first responder application of an automated external defibrillator (AED) before arrival of other emergency medical services (EMS) providers on scene, advanced life support, and postresuscitation care.…”
mentioning
confidence: 99%